CRIMEAN CONGO HEMORRHAGIC FEVER MANAGEMENT IN ERBIL DURING 2010-2011 - Abdullah S. Ibrahim; Kharman S. Ibrahim; Mohammed O. Mohammed; Mohammad A. Al-Shaikhani; Ali A. Barzanji; Sarhang J. Saeed; Saefadin Muhiaden; May N. Bhnam (European Scientific Journal, ESJ, 2014)
Crimean- Congo Hemorrhagic Fever (CCHF) is a viral zoonotic tickborn disease with a mortality rate of up to 50% in human. CCHF is caused by genus Nairovirus, in the family of Bunyaviridae, and can be transmitted to humans through the bite of ticks Hyalomma species or its contact with blood or tissues of CCHF patients or infected livestock. CCHF is a public health problem in many regions of the world e.g. Eastern Europe, Asia, Middle East, and Africa. The history of CCHF in Iraq shows that the disease has been detected in Iraq since 1979. During 2010-2011, five cases were referred to the infectious unit of Erbil teaching hospital on assumption of acute febrile illness, including some of them with hemorrhagic manifestations. Patients' serum samples were obtained at the time of admission and sent to the Central Public Health laboratory (CCHF.REF.LAB), Baghdad. Diagnosis was confirmed by ELISA for anti- CCHFV IgM. However, all of them that handled livestock had accounts of slaughtering animals within two weeks before symptom onset ,and the most commonly encountered symptom and signs were fever , malaise(100%) ,headache(80%) ,abdominal pain , myalgia, petechiae , ecchymosis(60%), nausea, vomiting, bleeding from gastrointestinal system, gingival, nose and vagina .Others include thrombocytopenia(100%), elevated liver enzymes(S.ASTandS.ALT) 80%,prolonged prothrombin time, anemia ,and Albuminuria (60%). Patients were treated following strict infection prevention measures and supporting circulation using intravenous fluid, blood with blood product support (platelet and fresh frozen plasma), with specific treatment with ribavirin .Thus, all of them positively responded to the treatment, and was cured, and discharged home.